COMPARISON OF FUNCTIONAL OUTCOME OF DYNAMIC CONDYLAR SCREW AND CONDYLAR BLADE PLATE IN TYPE A FRACTURES OF DISTAL FEMUR IN SKELETALLY MATURUE PATIENTS - Dilshad Gill; Muhammad Javaid Iqbal Awan; Osama Bin Saeed; Basharat Manzoor (Journal of University Medical & Dental College, 2021)
ABSTRACT BACKGROUND & OBJECTIVE: Distal femur fractures are increasingly common injuries in today’s orthopedic practice. Early treatment with suitable implant brings in promising functional outcomes. There is a growing debate over the type of implant used in these injuries. Therefore, we have compared two commonly used implants to determine the functional outcomes in search of an implant that has less post op complications, less technically demanding and produces better results. To compare the functional outcome of dynamic condylar screw with condylar blade plate in treatment of distal femur fractures. METHODOLOGY: A total of 372 skeletally mature patients aging 18-60 years of both gender with fracture distal femur (Type A, according to OTA classification) presented within 3 weeks of fracture time were included. Patients meeting inclusion criteria were stratified into two groups having 186 patients each. Group A and Group B. Group A received dynamic condylar screw fixation and in group B, condylar blade plate fixation was preferred. Patients were followed for 3 years and their Functional outcome was evaluated with the help of Lysholm Knee Score. RESULTS: Lysholm knee score after 3 years in group A (Dynamic condylar screw) was excellent (95-100) in 173 patients (76.9%), Good in 33 (17.7 %), Fair in 8 (4.3%), poor in 2 (1.1%).However, group B had Excellent in 57(30.6%), Good in 59(31.7%), Fair in 38 (20.4%), and poor in 32 (17.2%). CONCLUSION: Dynamic condylar screw can be used as an effective treatment with better functional outcome as compared to condylar blade plate in type A fractures of distal femur.